Akibat Hukum Terhadap Perjanjian Alih Debitur Atau Oper Kredit Tanpa Persetujuan Perusahaan Pembiayaan Dengan Objek Jaminan Fidusia Kendaraan Bermotor - Muhammad Harbitan Dinata; Noor Fatimah Mediawati; Sri Budi Purwaningsih (Indonesian Journal of Law and Economics Review, 2017)
In this globalization era, the needs of the society in finance activity has been increased, therefore, the finance companies got a great demand from the societies, particularly in the payment of vehicle.The frequent problem in the implementation of vehicle financing credit is the transition of the credit from debtors to new debtors without the approval of the Financing Company. The purpose of this study is to find out the impact of the law through the transitionagreement credit to the new debtors without the approval from the Financing Company. This study uses normative research with statute approach. The results showed that the legal consequences of the loan transfer agreement without the approval of the finance company resulted in the agreement is invalidsince it violated the objective terms of the agreement.The agreement of the credit transfer without the approval of the Financing Company violates the fiduciary guarantee law which prohibits the loan shift without prior approval of the Financing Company.This study give benefit and knowledge for the author, particularly for the societies about the legal consequences of credit transfer agreements without the approval of financing companies.